The Role of Sorong Container Terminal in Supporting the Sea Toll Program and Distribution of Goods to Remote Areas - Muhammad Idris; Fadel Muhammad; Muji Setiyono (Jurnal Ilmiah Manajemen Kesatuan, 2026)
Indonesia’s geographical structure as an archipelagic nation poses significant challenges for the equitable distribution of goods across its thousands of islands. This study analyzes the strategic role of Sorong Container Terminal in supporting Indonesia’s Sea Toll program and ensuring equitable goods distribution to remote regions in Eastern Indonesia. Using a mixed-methods approach, the research combines quantitative analysis of Key Performance Indicators (Yard Occupancy Ratio, Turnaround Time, and Berth Throughput) with qualitative evaluation of policy, infrastructure, and management strategies. Results indicate that the implementation of digital systems such as Enterprise Resource Planning (ERP) Centra, Terminal Operating System (TOS), and integrated ERP modules has improved operational efficiency, reducing ship waiting time and increasing container handling productivity. However, limited berth and yard capacity, weak multimodal coordination, and outdated land transport infrastructure remain major bottlenecks. Trend analysis projects container volume to rise to 113,802 Twenty-foot Equivalent Units (TEUs) by 2036, exceeding current capacity and underscoring the urgency of expansion. The study recommends strategic measures, including infrastructure modernization, digital integration, human resource development, and sustainable energy management, to enhance competitiveness. This finding indicates that Sorong Container Terminal demonstrates strong potential as a logistics hub, driving the success of the sea toll program and promoting balanced economic growth across Eastern Indonesia.